Design and development of wind tunnel for contraction ratio effects to the velocity and boundary layer thickness - Norlizaa, Mohamad (2012)
Wind tunnel is one of the tools that used in the aerodynamics research to recognize the air flow moving through a solid. It is not only been used in automotive but also in the construction of the building. Develop of the wind tunnel require specific parameters that need to be consider. Parameters such as contraction ratio and diffuser angle plays an important role to obtain a good result to the model. To have a better understanding about thermo fluids, the development of low speed wind tunnel are required. From the subsonic wind tunnel, the study is to determine the best contraction ratio of the flow quality of the air in the exit. The study is conducted by fabricate the low speed wind tunnel and by using Computational Fluids Dynamic (CFD) to obtain the data for different contraction ratio. The varying velocity and the boundary layer thickness between different contraction ratio will be attempted. The selection of the contraction ratio in designing the wind tunnel can affect the fluids flow. As the higher contraction ratio, the higher velocity at the test section can be obtained, reduced power loss and thin thickness of the boundary layer can achieved.